El derecho a defender el medio ambiente: la protección de los defensores y defensoras ambientales - Borrás, Susana (2013)
The increasing degradation of the environment and competitiveness on the exploitation of the natural limited resources demonstrates not only serious impacts on the environment, but also it generates important social impacts. The defenselessness which the victims of the environmental degradation face, as victims also of violations of human rights, has given origin to a movement of resistance led by the so called «environmental defenders», who, beyond the activism, try to protect the environment and to defend the most vulnerable groups affected by this type of environmental aggressions. This has led to the recent and worrying proliferation of abuses against the human rights of these people. The frequency of murders and threats that the defenders suffer, the infringement of the rights of its peoples and the subsequent impunity of the authors of these serious violations generate the need to point out the existing problems in the identification of this reality, in its recognition and legal protection and of analyzing which is the protection and assistance, that from the international area, these persons are awarded in situation of high risk.